The Influence Of Team-Based Learning On Students' Understanding Of Patient Safety: A Literature Review - Duhu, Ludovikus; Kusumawati, Wiwik (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Patient safety is a form of health service that is safe for patients. To increase students' understanding of patient safety, teachers need to use teaching methods that are interesting to students. Team-based learning (TBL) is an active learning model in small teams that is expected to equip students with patient safety skills. This study aims to determine the effect of TBL on students' understanding of patient safety by reviewing the literature. Article searches were carried out through three databases, namely Scopus, PubMed, and Science Direct. Search results using the keywords "team-based learning", "patient safety," and "students" found 10,843 articles. From the articles collected, the researchers screened for duplicates and suitability of titles and abstracts, and the results found 121 articles. Of the 121 articles, researchers screened them again using the Joanna Briggs Institute (JBI) instrument and adjusted the inclusion criteria to obtain 7 articles that met the review requirements. The results of this literature review show four themes of the influence of TBL on student learning: TBL increases understanding of patient safety concepts, develops critical thinking skills, and encourages active student participation in learning, communication, and teamwork. It was also found that three factors supported the success of TBL in increasing understanding of patient safety: trained facilitators, learning material design, and formative evaluation.